2022
DOI: 10.1177/03635465221093809
|View full text |Cite
|
Sign up to set email alerts
|

A Propensity Score–Matched Comparison Between Knotless Layer-by-Layer and En Masse Suture Bridge Techniques for Delaminated Rotator Cuff Tears

Abstract: Background: Because the articular layer is more prone to retraction than the bursal layer of the supraspinatus tendon, it is important to restore each layer anatomically while repairing delaminated rotator cuff tears (RCTs). Purpose: To compare clinical outcomes and tendon integrity between knotless layer–by–layer and conventional en masse repair techniques for delaminated RCTs. Study Design: Cohort study; Level of evidence, 3. Methods: We retrospectively reviewed data from 174 consecutive patients with delami… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
31
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(33 citation statements)
references
References 29 publications
(45 reference statements)
1
31
1
Order By: Relevance
“…Among the 11 studies, we removed 5, as 1 study 33 was written in Chinese, 1 study 29 included partial rotator cuff tears, 2 studies 12,18 restored only the bursal layer, and 1 study 3 included nondelaminated rotator cuff tears. In the end, 1 RCT 21 and 5 observational studies 11,15,16,28,30 were included in this meta-analysis. Figure 1 presents the flowchart for the study-inclusion process.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the 11 studies, we removed 5, as 1 study 33 was written in Chinese, 1 study 29 included partial rotator cuff tears, 2 studies 12,18 restored only the bursal layer, and 1 study 3 included nondelaminated rotator cuff tears. In the end, 1 RCT 21 and 5 observational studies 11,15,16,28,30 were included in this meta-analysis. Figure 1 presents the flowchart for the study-inclusion process.…”
Section: Resultsmentioning
confidence: 99%
“…Some have reported that the DL technique can have a better clinical outcome, and others have reported that both techniques have equivalent outcomes. 4,16…”
mentioning
confidence: 99%
“…One of the main goals of rotator cuff repair surgery is to relieve pain and restore shoulder function. A recent study from Kim et al 19 used en masse suture bridge techniques for full-thickness supraspinatus tears. At the final follow-up, the VAS, Constant, ASES, and UCLA scores were 1.1 ± 0.9, 84.3 ± 16.4, 88.3 ± 17.4, and 31.1 ± 6.0, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Rotator cuff tears are one of the most common causes of shoulder pain and dysfunction, and arthroscopic repair is an effective treatment for rotator cuff tears. 9 , 19 There are many surgical methods for rotator cuff repair, including single-row or double-row anchor repair technology, layer-by-layer suture bridge technology, transosseous tunnel technology, and patch augmentation technology. The objective of these methods is to reattach the torn tendon to its footprint and fix it to create favorable conditions for tendon-bone healing at the native enthesis of the rotator cuff.…”
mentioning
confidence: 99%
“…The other method is a layered suture under arthroscopy, which adheres to the original anatomical structure of the rotator cuff by separately fixing the synovial sac of the rotator cuff and the lateral aspect of the joint. No significant difference was observed between separate and en bloc repairs [11, 12], it is unclear if tendon delamination affects rotator cuff repair healing and clinical outcomes. Delamination is a risk factor for poor clinical and anatomical outcomes after rotator cuff repair [2, 13, 14].…”
Section: Introductionmentioning
confidence: 99%